The Design of Monitoring Application Web-Based Quality Control in Utama Raya Motor Industri - Kusyadi, Irpan (Jurnal Informatika Universitas Pamulang, 2019)
This research was made to develop the management of PT. Utama Raya Motor Industri. In monitoring often occur delays in the process of making reports both daily and monthly in the quality control section. Thus it is necessary to improve in the process of making reports both daily and monthly. Therefore, an application program is needed that can be used by web-based admin quality control as a tool in making reports. With the implementation of the monitoring quality control application design at PT. Utama Raya Motor Industry, which has very high processing capabilities and saves memory. So that the company or agency can achieve the goals that have been set optimally and accurately. In this research has been able to provide a web-based quality control monitoring application program at PT. Utama Raya Motor Industri. With this application, admin quality control can monitor quality easily and quickly.